The organization of technological co-operation of transport types in transloading points of loads - Нефьодов, Микола Анатолійович; Пономарьова, Надія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2012)
The question of research of technological process elements co-operation of transport types is examined with the use of the progressive transport-technological systems (TTS)